2009
DOI: 10.1021/ma802529h
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Porous and Wrinkled Fibers of Polystyrene Electrospun from Dimethylformamide

Abstract: Submicron diameter fibers of polystyrene are electrospun from solutions in dimethylformamide (DMF). When electrospun in a high-humidity environment, the interior of these fibers was found to be highly porous rather than consolidated, despite the smooth and nonporous appearance of the fiber surfaces. The formation of interior porosity is attributed to the miscibility of water, a nonsolvent for the polymers in solution, with DMF. The resulting morphology is a consequence of the relatively rapid diffusion of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
263
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(277 citation statements)
references
References 51 publications
13
263
1
Order By: Relevance
“…The miscibility of water with solvent causes formation of liquid-liquid phase separation and finally porous features within the fibers occur. Recently, Pai et al reported interior porosity of polystyrene fibers prepared from DMF at different levels of humidity and influence of this internal morphology on mechanical strength and stiffness of the electrospun fibers [15]. The same group also pointed out the development of wrinkled surface topography of fibers that result from buckling instability of the charged jet in poly(acrylonitrile) (PAN) and PS.…”
Section: Introductionmentioning
confidence: 99%
“…The miscibility of water with solvent causes formation of liquid-liquid phase separation and finally porous features within the fibers occur. Recently, Pai et al reported interior porosity of polystyrene fibers prepared from DMF at different levels of humidity and influence of this internal morphology on mechanical strength and stiffness of the electrospun fibers [15]. The same group also pointed out the development of wrinkled surface topography of fibers that result from buckling instability of the charged jet in poly(acrylonitrile) (PAN) and PS.…”
Section: Introductionmentioning
confidence: 99%
“…The reason behind this is not fully understood. Surface roughness of electro-spun fibres has been addressed widely (Milleret et al, 2012;Sawawi et al, 2013) and ascribed to process conditions during electro-spinning such as humidity, polymer concentration, and the type of solvent used (Casper et al, 2003;Pai et al, 2009). Increase in the surface roughness of the fibres after onset of degradation in PBS solution at 37°C has been reported for electro-spun poly(lactic-co-glycolic acid) (Duan et al, 2007) and DegraPol® (Henry et al, 2007) scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…The simulations of Kyu and co-workers [1,[12][13] predicted morphologies that ranged from smooth hollow fibers, to fibers with a smooth surface and porous core, to fibers with porous morphologies both at the fiber surface and in the core. Chia-Ling Pai et al [14] experimentally confirmed the electrospun fibers exhibiting a smooth fiber surface and porous 5th International Conference on Advanced Design and Manufacturing Engineering (ICADME 2015) interior. They found that fibers with a smooth surface and porous.…”
Section: Introductionmentioning
confidence: 94%